POSITIVE POLITENESS STRATEGIES IN JAY SHETTY PODCAST YOUTUBE CHANNEL: AN INTERVIEW WITH WILL SMITH - TASRUL DONI WAHDANI; PEPI SITI PATUROHMAH; R. MYRNA NUR SAKINAH (LINGUISTICA, 2023)
This study aims to examine the positive politeness strategies that are often used to show similarity, familiarity and respect. This research discusses the positive politeness strategies used by Jay Shetty on the Jay Shetty Podcast YouTube channel. This research focuses on the types of positive politeness strategies used by Jay Shetty to Will Smith as the guest star in talk show videos on the Jay Shetty Podcast YouTube channel. The data from this study are analyzed using the theory proposed by Brown & Levinson (1987) who argue that there are 15 positive politeness strategies. The method used to analyze this research is a qualitative approach with the content analysis method, the data in this study are taken from Jay Shetty's interviews with Will Smith that have been transcribed. The results showed that Jay Shetty used 10 out of 15 positive politeness strategies proposed by Brown & Levinson (1987) when he communicated with the guest star, with a total of 75 data. Based on the analysis, the positive politeness strategy of exaggerate (approval, interest, sympathy with H) is the most dominant strategy used by Jay Shetty with a total of 21 data. Jay Shetty uses this strategy to show respect, approval, interest and sympathy to his guest star so that they are satisfied.